AMERICANIZING ISLAM AS THE PRICE OF ASSIMILATION - Morgan, John H (SCAD Independent, 2014)
This essay is an exploration into the social inevitabilities of culture shifts within the American Muslim communityâ€™s self-understanding of their faith. Rather than a theological explication of the reasons why and why not Islam may or can or will not assimilate in America, our approach will be strictly sociological thereby side stepping the intricate dialectic of theological niceties in deference to the social realities of culture change. As a social psychologist, my duty is to acknowledge the inevitabilities of behavioral shifts brought about due to social and cultural pressures resulting from immigration into an alien cultural weltanschauung, i.e., worldview. Therefore in this essay, we will explicate the meaning and nature of de-ethnicization and re-enculturation as we endeavor to disentangle religion from culture, recognizing that much of what goes under the flag of religious orthodoxy is really culturally-mandated behavior and worldview. The assimilation process, however, will bear heavily upon the necessity for Muslim clergy in America to become professional by Western standards and we will in the process explore the complexities of religious secularism as a way of becoming an â€œAmericanâ€ Muslim. Finally, we will suggest liturgical and architectural â€œadjustmentsâ€ to Western modes of public worship while indicating linguistic niceties which will prove helpful in the assimilation process which we have chosen here to call the â€œIslamicization of Americaâ€.